Porous Materials Confining Single Atoms for Catalysis - Zhu, Tao; Han, Yiwei; Liu, Shuai; Yuan, Bo; Liu, Yatao; Ma, Hongli (Frontiers in Chemistry, 2021)
In recent years, single-atom catalysts (SACs) have received extensive attention due to their unique structure and excellent performance. Currently, a variety of porous materials are used as confined single-atom catalysts, such as zeolites, metal-organic frameworks (MOFs), or carbon nitride (CN). The support plays a key role in determining the coordination structure of the catalytic metal center and its catalytic performance. For example, the strong interaction between the metal and the carrier induces the charge transfer between the metal and the carrier, and ultimately affects the catalytic behavior of the single-atom catalyst. Porous materials have unique chemical and physical properties including high specific surface area, adjustable acidity and shape selectivity (such as zeolites), and are rational support materials for confined single atoms, which arouse research interest in this field. This review surveys the latest research progress of confined single-atom catalysts for porous materials, which mainly include zeolites, CN and MOFs. The preparation methods, characterizations, application fields, and the interaction between metal atoms and porous support materials of porous material confined single-atom catalysts are discussed. And we prospect for the application prospects and challenges of porous material confined single-atom catalysts.